Energy dissipation properties of backfill materials under compaction in solid waste backfill mining - Yu, Bangyong; He, Xu; Zhang, Ying; Jiang, Jinglin; Li, Ang; Li, Zhen (Frontiers in Materials, 2025)
The compaction of backfill materials is critical in Solid Waste Backfill Mining (SWBM) systems, as it can reduce the chance of dynamic hazards effectively. Despite its importance, the compaction and energy dissipation properties of backfill materials are still not fully understood. In this research, a series of laboratory tests were conducted to explore the deformation, particle morphology, and energy dissipation properties of gangue particles. The results indicated that the process of axial strain increase encompassed three stages: rapid increase (0∼2 MPa) stage, slow increase (2∼8 MPa) stage, and slight increase (8∼16 MPa) stage. For the specimen (n = 0.4), the particle flatness ranges from 1.38 to 1.75 and decreases gradually with some fluctuations. The total surface area and particle crushing energy exhibit a similar trend, both increasing monotonically with the increase of axial stress, varying within 0.688∼2.092 m2 and 4.81∼14.35 kJ/m3, respectively. The relationship between particle crushing energy and axial strain is approximated by a linear function. The energy consumed by particle breakage constitutes a small proportion (0.7%∼7.8%) of the total energy consumption for specimen deformation, while the majority of energy consumption is attributed to inter-particle friction, especially in the later compaction stage. However, the initial particle size distribution has negligible influence on the total surface area and particle crushing energy.